Desgaste dental erosivo y consumo de frutas y bebidas en escolares de 12-18 años - Camargo Boyacá, Juan Esteban; Castañeda Villalba, Karen Julieth; Gutiérrez Camacho, Yerly Tatiana; Pérez Gasca, Dailyn Juliana (Universidad Antonio Nariño, 2023)
Objective: To establish the risk of dental erosion related to the consumption of fruits and beverages in a group of school children between 12 and 18 years of age. Methodology: An observational cross-sectional study was carried out in two schools in Bogota, from which a sample of 85 participants was obtained, to whom a previously approved and validated survey was applied, using a form of 24 questions based on the risk factors related to erosive dental wear in adolescents. Results: it was obtained that of the 12 fruits evaluated, 67% of them were classified as erosive and when a combination of them was made, 29% of the students mixed the combined fruits and classified them as Erosive with Extremely Erosive; it also became evident that 35% of the students who consumed these fruits were female. Conclusion: There is a high risk that the study population may present erosive dental wear with the passage of time due to poor consumption habits of acidic fruits and drinks, classified as extremely erosive and erosive; especially the female sex, since it was found that they are the ones who consume and combine these types of fruits and fruit juices the most.